Attitude estimation and stabilization of a quadrotor aircraft - Ghashghaee, Fereshteh (My University, 2011)
In the past few years, researchers have shown great interest in quadrotor aircraft as a platform for UAV research due to simplicity of construction as well as maintenance, ability to hover in small indoor locations or hazardous environments, vertical take-off and landing capability, etc. Attitude stabilization of a quadrotor requires accurate information about current orientation of the vehicle. With the emergence of Micro-Electro-Mechanical System (MEMS) sensors, a relatively cost-effective way for attitude estimation consists of using gyroscope, accelerometer and magnetometer devices strapped down on vehicle’s center of mass. A number of previous works deal with fusing angular velocity with measurements of accelerometer and magnetometer to construct an estimation of aircraft orientation.
Keywords: Quadrotor aircraft; Attitude estimation; Attitude stabilization